Time-varying controller design for input saturated systems. Issue 15 (October 2020) - Wang, Qian; Zhang, Zhiqiang; Zhang, Kai; Lin, Qingxia
Abstract: This paper presents a time-varying controller design for input saturated system whose poles are all in the closed left-half plane by introducing a time-varying parameter. The time-varying state feedback controller and the observer-based time-varying output feedback controller are both designed based on the parametric Riccati equation and parametric Lyapunov equation to ensure the exponential stability of the closed-loop system. The dynamic performance improvement of the closed-loop system is obtained by the designed controllers. The effectiveness and the usefulness of the proposed method are illustrated by the numerical simulation.